Sistematización de la experiencia de radio mensaje en el campo de la salud en la comunidad de Cayambe como instrumento de desarrollo local 1990 a 2010 - Paz Ruiz, Manolo Sebastián (2015)
This research work is guided in the Latin American communication, education, and development studies. The topics addressed are: book, educational communication for development, popular and participatory communication, and regional radio for development. Outstanding authors such as Rosa María Alfaro, Paulo Freire and Mario Kaplún, among others, giving us an expanded vision of the above concepts and the relationship between them. Is addresses the thematic of the radio in the Ecuador, the historical context, the popular radios and its frequencies of the public and prívate radios in the country, this will allow discover the tour of them radios and as went his proposed communication to a process of transformation social. Likewise, the background and story of "Radio message" which is the central axis of the research, and its relationship to "Maternity leave half of the world" of Cayambe. We consider of transendential importance addressing public politics, identifying the principal propouse of the National Plan of good living to apply the experience of Radio message. The Field research allowed a concrete approach to the object of study. Techniques of data collection were used through interviews and observation guides. And we realice the analysis of FODA with this can identify the opportunities, weaknesses and threats. Atthis point it is identifying if the "Radio message" as a way of communication has managed to interview in development and progress, and above all in the quality of medical care for the population of Cayambe.